A novel microsurgical anastomosis training model using gradually thawed cryopreserved microvessels of rat cadavers. Issue 7 (July 2018) - Safi, Ali-Farid; Safi, Sema; Tayeh, Mahmoud; Timmer, Marco; Goldbrunner, Roland; Kauke, Martin
Abstract: In consideration of the 3-R-rule (Refine-Replace-Reduce) as a guideline for promoting ethical use of animals for surgical training, we present a novel training model for microvessel anastomosis. In a rat cadaveric study, we evaluated the surgical anatomy of the common carotid artery (CCA), external jugular vein (EJV) and femoral vessels (FV) which were then used as templates for the present investigation. Anatomical dissection of 30 rat cadavers was performed. Two residents without prior microsurgical experience were included in the study and performed 5 CCA, 5 femoral artery, 5 EJV and 5 femoral vein anastomoses. Patency and leakage served as qualitative variables and operation time as a quantitative variable for efficiency control. The average time improved for arterial and venous anastomoses (45 min–22 and 60 to 32 min, respectively) for both surgeons. While both surgeons experienced patency failure or leakage within the first half of performed arterial and venous anastomoses, they could improve to a 100% patency rate without the occurrence of leakage for the last half of trials. The rat head & neck anatomy presents various characteristics related to the harvest of the vessels of interest. We provide anatomical knowledge about the topography related to the harvest of the CCA, EJV, and FV. Our model is an easily accessible, low-cost microsurgical simulation model, allowing a realistic and instructive performance of anastomoses. Since cadaveric vessels are used, an approval of the local ethics committee is not needed.